2022
DOI: 10.1371/journal.pone.0271233
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of indirect markers of muscle damage following lower limbs eccentric-biased exercises: A systematic review with meta-analysis

Abstract: Purpose The aim of this review was to (1) characterize the time-course of markers of exercise-induced muscle damage (EIMD) based on the level of maximal voluntary contraction torque loss at 24-48h post-exercise (MVCloss24-48h), (2) identify factors (e.g., exercise and population characteristics) affecting the level of MVCloss24-48h, and (3) evaluate the appropriateness of EIMD markers as indicators of MVCloss24-48h. Methods Magnitude of change of each EIMD markers was normalized using the standardized mean d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…In line with previous studies (29,30) that compared two loaded walking bouts (slope, −28%; velocity, 5 km·h −1 ; load, 10% of body mass, 1 wk apart), the results of the present study showed a protective effect of Ex1 on Ex2 (i.e., RBE). Similar to these previous studies, we found a prolonged MVC torque loss (i.e., >24 h after the exercise) of the knee extensors after Ex1 (~20%–25%; moderate muscle damage (2,3)), whereas MVC torque had already recovered 24 h after Ex2. Moreover, muscle soreness, another marker of EIMD (1,3), was less affected after Ex2 compared with Ex1.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with previous studies (29,30) that compared two loaded walking bouts (slope, −28%; velocity, 5 km·h −1 ; load, 10% of body mass, 1 wk apart), the results of the present study showed a protective effect of Ex1 on Ex2 (i.e., RBE). Similar to these previous studies, we found a prolonged MVC torque loss (i.e., >24 h after the exercise) of the knee extensors after Ex1 (~20%–25%; moderate muscle damage (2,3)), whereas MVC torque had already recovered 24 h after Ex2. Moreover, muscle soreness, another marker of EIMD (1,3), was less affected after Ex2 compared with Ex1.…”
Section: Discussionsupporting
confidence: 90%
“…Participants performed 2 bouts of downhill walking on a treadmill for 45 min while carrying a load equivalent to 30% of their body mass (treadmill gradient: −25 %, speed: 4.5 km·h −1 ) separated by 14 d (top). During exercises, rating of perceived exertion (red), gas exchanges (green), heart rate (blue), muscle activity (orange) of the Rectus femoris (1), Vastus lateralis (2) and Biceps femoris (3), and the spatio-temporal parameters (red) were obtained during walking.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the present findings, previous studies have generally found either low or no significant correlations between these commonly used markers. For example, a recent meta-analysis of 141 lower limb ECC studies found that the reduction in MVC was poorly associated (r 2 < 0.28) with soreness and likewise poorly correlated (r 2 < 0.21) to serum CK activity (31). The majority of previous studies have similarly shown no significant relationships between muscle soreness and CK activity after ECC (32)(33)(34)(35), although notably Kim et al (36) did find that CK activity and soreness were weakly correlated (r 2 < 0.11) in a cohort of high-responding subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A common approach to investigating the muscle regeneration capacity is by inducing damage through repeated efforts of maximal to near-maximal eccentric lengthening contractions—a force applied to the muscle that exceeds the torque produced by the muscle itself [ 90 ]. The high mechanical stress induced by these contractions leads to focal microlesions of the sarcomeres as well as the extracellular matrix and connective tissue of the muscle fibers [ 91 ], which manifests itself by a range of clinical symptoms such as delayed-onset muscle soreness (DOMS), muscle stiffness, swelling, decreased proprioceptive function, and loss in maximal force-generating capacity [ 92 ].…”
Section: Clinical Interventions Supporting the Consumption Of N-3 Puf...mentioning
confidence: 99%